Post-Salafism: religious revisionism in contemporary Saudi Arabia - Sinani, Besnik (Religions, 2022)
This article seeks to identify the driving factors, features, and significance of the transformation of Salafism in contemporary Muslim societies, a development labeled ‘post-Salafism’. Throughout the 20th century, Salafism grew into a global religious movement, with distinctive local characteristics. Its post-Salafi transformations have likewise been diverse and reflect local conditions. ‘Post-Salafism’ is a term employed congruently to point at the fragmentation of Salafi religious authority; the emergence of Salafi alliances with other Muslim groups, which challenge Salafi conceptions of doctrinal superiority; in Salafi softening of sectarian rhetoric as a way of distancing from militant groups; in Salafi “indigenization”; and in social and political transformations that overlap with post-Islamism. Post-Salafism refers additionally to debates within Salafi circles, reflective of emerging internal doctrinal contradictions. Since the founding of Saudi Arabia in 1932, the kingdom has played a unique role in promoting, financing, and building the institutional network of global Salafism. The transformation of Saudi Salafism, therefore, resulting from changes in government policy, public pressure, and internal revisionism, will effect Salafism globally, pointing at a transformative moment in Muslim religious thought and authority structures.